ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA BERTIPE HOTS BERDASAR TEORI NEWMAN - wilda mahmudah (Unisda Journal of Mathematics and Computer Science (UJMC), 2018)
The results of the PISA survey in 2015 show that Indonesian students' learning outcomes are low, ranked 63 out of 69 countries evaluated. Indonesian students are still difficulty in answering questions that require reason. In 2017 revised curriculum 2013, developed math problems based hots. Problem based hots require the ability to think high level and enter theprocess of reasoning. In National Examination 2018 there is about 10% of the problem based hots, the results obtained 40% of students difficulty about that. This research aimed to analize of student error in solving math problems based hots by Newman theory. This research is qualitative descriptive. The subjects of research were VIII-G grade students of SMP Negeri 1 Gresik. Data collection techniques using tests. An analysis framework wasdeveloped basedon Newman’s error categories. The results of research were obtained 4 types of errors with percentage were comprehension errors65%, transformation errors 30%, processing errors 10%. The results showed that comprehension errors is the more dominant errors than the other. In general, the factors causing the error is reasoning ability and skills of students who are low in the problems solving on real context and manipulating it into algebraic form